A QUALITATIVE APPROACH OF THE ASSOCIATION BETWEEN THE TODDLER'S ATTACHMENT STYLE AND THE DYADIC INTERACTION WITH THE MOTHER - ANDREEA M. IONESCU; CARMEN COSTEA-BĂRLUŢIU (Studia Universitatis Babes-Bolyai, 2016)
ABSTRACT. The quality of toddler's experience with the caregiver impacts the structuring of the internal working models of attachment (Bowlby, 1980, 1988), further used as means of comfort and security, and prototypes for later close relationships. Using inductive qualitative techniques, our study aims to describe specific schemes of mothertoddler interaction, for each of the attachment styles. Semi-structured interactions of 27 mother-child dyads were videotaped in their familiar environment and the films were qualitatively analyzed, for each group of toddlers previously identified as having the same attachment style. The interactions of secure toddlers and their mothers were marked by synchronized actions, joy of interacting, closeness, and security. Mothers of ambivalent children displayed a more dominant action, with discordances between the social and psychological level of communication. Avoidant toddler-mother dyads presented a higher balance between their relational spaces, maintaining contact, with a low level of intimacy. The absence of a coherent strategy defined the interaction between the toddlers with disorganized attachment and their mothers. Our results confirm previous findings in the field of attachment in early childhood and add up to these results by providing a methodology to approach these interactions and the use of video recordings as ways to develop interventions aiming to increase the attachment security.